Strategic planning workbook - Lake, Neville (Kogan Page LondonGB, 2002)
Provides a practical guide to the seven key stages involved in strategic planning viz. strategic thinking; understanding the strategic context; understanding your business; analysis and decision making; action planning; putting it in writing; and, implementation.